2024
DOI: 10.1093/cvr/cvae095
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin inhibits increased Na influx in atrial cardiomyocytes of patients with HFpEF

Maximilian Trum,
Johannes Riechel,
Elisa Schollmeier
et al.

Abstract: Aims Heart failure with preserved ejection fraction (HFpEF) causes substantial morbidity and mortality. Importantly, atrial remodeling and atrial fibrillation is frequently observed in HFpEF. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) have recently been shown to improve clinical outcomes in HFpEF, and post-hoc analyses suggest atrial antiarrhythmic effects. We tested if isolated human atrial cardiomyocytes from patients with HFpEF exhibit an increased Na influx, which is known to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, we showed for the first time that intracellular Na + entry and Na + concentration are higher in the atrial myocytes of patients with HFpEF, a condition in which SDB is very common, which could contribute to atrial contractile dysfunction and arrhythmias ( Trum et al, 2024 ). Interestingly, we also showed that patients with SDB have increased late Na + current in their remodeled atria, which could contribute to intracellular Na + overload ( Lebek et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed for the first time that intracellular Na + entry and Na + concentration are higher in the atrial myocytes of patients with HFpEF, a condition in which SDB is very common, which could contribute to atrial contractile dysfunction and arrhythmias ( Trum et al, 2024 ). Interestingly, we also showed that patients with SDB have increased late Na + current in their remodeled atria, which could contribute to intracellular Na + overload ( Lebek et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear whether myocardial Na + concentration is actually affected by the altered Na + currents in SDB. Recently, we demonstrated for the first time that intracellular Na + entry and Na + concentration were higher in the atrial myocytes of patients with heart failure and preserved ejection fraction—conditions in which SDB is very common ( Trum et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%